The Effect of Stick Puppet As a Medium on Students’ Speaking Skill in Narrative Text at SMK Dian Indonesia : Efek Boneka Tongkat Sebagai Media dalam Keterampilan Bicara Siswa Pada Teks Narasi di SMK Dian Indonesia - Wyndis Faradita Febryanti; Dian Rahma Santoso (Academia Open, 2023)
The aim of this study was to find out there was any significant effect in learning speaking narrative using stick puppet as a medium in their storytelling. The background of this research has been conducted on eleventh TKJ students of SMK Dian Indonesia who have problems understanding in English learning especially in speaking skill. Research design which the researcher used was pre-expperimental one class research. The result of the Researcher used the standart 5% or 0.050. After consulted to t – table, the result is : tvalue ≥ ttable (14; 5% or 0.050) = 6,87 ≥ 1,76. After calculate it, the researcher count the value of Eta-square and the result was there is a significant effect of using the medium. Thus, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. Based on the result above, there is significant effect of stick puppet as media on students’speaking skill in narrative text at SMK Dian Indonesia. Highlights: Innovative Teaching Medium: Stick puppet as a storytelling tool offers a creative approach to enhance speaking skills. Significant Effect: The research highlights the positive impact of stick puppet usage on students' narrative speaking abilities. Educational Implications: Findings suggest the potential for integrating unconventional mediums like stick puppets into language learning curriculum to address specific learning challenges. Keywords: Stick Puppet, Speaking Skill, Medium